Geopolitics of Arctic shipping: the state of icebreakers and future needs. (3rd April 2018) - Drewniak, Megan; Dalaklis, Dimitrios; Kitada, Momoko; Ölçer, Aykut; Ballini, Fabio
ABSTRACT: The starting point of the analysis in hand is a brief discussion of the so-called 'Arctic Passages.' Considering that ice and ice-pacts will remain a concern in the future, the support of icebreakers will still be needed to facilitate the safe passage of ships. Describing the state of these types of vessels currently available is the main aim, with a particular focus on key state players: the Russian Federation (RF), the United States of America (USA) and Canada. Additionally, a critical evaluation of future plans in relation to the introduction of icebreakers into service is taking place. Russia has already built and operates a certain number of vessels that are fully capable to handle current traffic demands, as well as the expected future increase. On the opposite direction, both Canada and USA are facing problems to deal with current demands and the situation during the next couple of years looks rather troublesome. Their obvious lack of icebreaking capabilities is somewhat disconcerting given the expected demand in the Arctic region in coming years coupled with the lengthy acquisition and production process required for a new icebreaking fleet. An acceleration of their acquisition plans and activities to cover the identified gap in icebreakers' services is clearly a high priority.